Letter (copy) : International Solidarity Fund - Help for Children of Spain - Tewson, Vincent
1938-11-08 038-0114-001 Secretary's. FC/99. 8th November, 1938. Mr. C. Hargreaves, The Nelson & District Weavers' Association, Pendle Street, NELSON. Dear Mr. Hargreaves, INTERNATIONAL SOLIDARITY FUND - HELP FOR CHILDREN OF SPAIN. I thank you for your letter of the 5th instant stating that the Officials of your Association are contemplating making a contribution towards the relief of suffering amongst the child victims of the Spanish war, and asking us to suggest the fund to which they should contribute. As your Association are no doubt aware, the National Council of Labour have issued from time to time appeals for contributions to the International Solidarity Fund. This Fund is administered by a Joint Committee of the International Federation of Trade Unions and the Labour and Socialist International, and an official committee in Spain is charged with the responsibility of advising in regard to commodities required and the receiving and distribution of consignments sent to Spain. Special attention is, of course, paid to the needs of the children, and I think the best thing I can do is to send you an extract from the report of the General Council made to the Blackpool Congress in September which will give you particulars of the help given to the children through the medium of the International Solidarity Fund. With the winter months ahead help is still more urgently needed for the supplying of warm clothing 292/946/38/114(I)